Spanish version of the Kidney Disease Knowledge Survey (KiKS) in Peru: cross-cultural adaptation and validation - Mota Anaya,Evelin (2016)
INTRODUCTION Chronic kidney disease (CKD) affects 50 million people globally. Several studies show the importance of implementing interventions that enhance patients’ knowledge about their disease. In 2011 the Kidney Disease Knowledge Survey (KiKS) was developed: a questionnaire that assesses the specific knowledge about chronic kidney disease in pre-dialysis patients. OBJECTIVE To translate to Spanish, culturally adapt and validate the Kidney Disease Knowledge Survey questionnaire in a population of patients with pre-dialysis chronic kidney disease. METHODS We carried out a Spanish translation and cross-cultural adaptation of the Kidney Disease Knowledge Survey questionnaire. Subsequently, we determined its validity and reliability. We determined the validity through construct validity; and reliability by evaluating its internal consistency and its intra- observer reliability (test-retest). RESULTS We found a good internal consistency (Kuder-Richardson = 0.85). The intra-observer reliability was measured by the intra-class correlation coefficient that yielded a value of 0.78 (95% CI: 0.5-1.0). This value indicated a good reproducibility; also, the mean difference of -1.1 test-retest SD 6.0 (p = 0.369) confirms this finding. CONCLUSION The translated Spanish version of the Kidney Disease Knowledge Survey is acceptable and equivalent to the original version; it also has a good reliability, validity and reproducibility. Therefore, it can be used in a population of patients with pre-dialysis chronic kidney disease.